Penerapan Media Cerita Bergambar pada Pembelajaran Bahasa Indonesia Kelas V MI Miftahul Falah - Maftuhah, Siti; Al Sana, Tana Lina Muzna (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
This research aims to determine the application of picture story media and the results of the application of picture story media in fifth-grade Bahasa Indonesia learning at Madrasah Ibtidaiyah. This research uses qualitative methods with data sources from interviews and observations. The data obtained was then analyzed to obtain a general picture of the application of picture story media in fifth-grade Bahasa Indonesia learning at Madrasah Ibtidaiyah Miftahul Falah. The results of the research show that there are changes experienced by students after being taught picture story media. These changes can be seen from an increase in the quality of student learning, students become more receptive to the material presented by the teacher and can stimulate students’ imaginations to think creatively during the ongoing learning process. So that teachers get choices in carrying out the Bahasa Indonesia learning process.